Effect of Non‐Chlorinated Mixed Solvents on Charge Transport and Morphology of Solution‐Processed Polymer Field‐Effect Transistors. (3rd March 2014) - Lee, Wen‐Ya; Giri, Gaurav; Diao, Ying; Tassone, Christopher J.; Matthews, James R.; Sorensen, Michael L.; Mannsfeld, Stefan C. B.; Chen, Wen‐Chang; Fong, Hon H.; Tok, Jeffrey B.‐H.; Toney, Michael F.; He, Mingqian; et al.
<x xml:space="preserve">Abstract</x> Using non‐chlorinated solvents for polymer device fabrication is highly desirable to avoid the negative environmental and health effects of chlorinated solvents. Here, a non‐chlorinated mixed solvent system, composed by a mixture of tetrahydronaphthalene and p‐xylene, is described for processing a high mobility donor‐acceptor fused thiophene‐diketopyrrolopyrrole copolymer (PTDPPTFT4) in thin film transistors. The effects of the use of a mixed solvent system on the device performance, e.g., charge transport, morphology, and molecular packing, are investigated. p‐Xylene is chosen to promote polymer aggregation in solution, while a higher boiling point solvent, tetrahydronaphthalene, is used to allow a longer evaporation time and better solubility, which further facilitates morphological tuning. By optimizing the ratio of the two solvents, the charge transport characteristics of the polymer semiconductor device are observed to significantly improve for polymer devices deposited by spin coating and solution shearing. Average charge carrier mobilities of 3.13 cm2 V−1 s−1 and a maximum value as high as 3.94 cm2 V−1 s−1 are obtained by solution shearing. The combination of non‐chlorinated mixed solvents and the solution shearing film deposition provide a practical and environmentally‐friendly approach to achieve high performance polymer transistor devices.